The Effect of Achievement Motivation Training and Religiosity on Learning Achievement for Indonesian Muslim University Students - Hera Mutiara Arsyad; Siti Haerani; Dian A.S Parawansa (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to ascertain the impact of training in accomplishment motivation, religiosity on learning achievement for Indonesian Muslim University students. Quantitative research is the method employed. Students from the Faculty of Economics and Business made up the study's population. at the Indonesian Muslim University and the sample was taken using a purposive sampling technique. Multiple linear regression analysis methods, the traditional assumption test, the R2 test, and the t test were employed in the data analysis. The findings of this study demonstrate that religiousness has a big impact on learning performance and that achievement motivation training has a large impact on both student success in the Faculty of Economics, Muslim University of Indonesia. Keywords :Achievement Motivation Training, Religiosity and Learning Achievement